2013
DOI: 10.1177/1938640013501544
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Radiological Study of Peroneal Tendon Pathology

Abstract: Patients with MRI findings of peroneal tendon pathology should undergo careful clinical examination, as the positive predictive value of MRI for peroneal tendon pathology with actual clinical findings is low. This study demonstrates that peroneal tendon tears are often incidental findings on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…While the data in the current study demonstrated that tendoscopy and MRI were in agreement for only 67% of diagnoses, MRI still provided information helpful for preoperative planning. A previous study by Giza et al 7 demonstrated the importance of MRI in preoperative planning for the peroneal tendons. The authors found that only 27 of 56 patients (48%) who had peroneal pathology diagnosed on MRI also had a positive clinical exam.…”
Section: Discussionmentioning
confidence: 99%
“…While the data in the current study demonstrated that tendoscopy and MRI were in agreement for only 67% of diagnoses, MRI still provided information helpful for preoperative planning. A previous study by Giza et al 7 demonstrated the importance of MRI in preoperative planning for the peroneal tendons. The authors found that only 27 of 56 patients (48%) who had peroneal pathology diagnosed on MRI also had a positive clinical exam.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to diagnosis, MRI and ultrasound techniques may be used to identify pathophysiological changes (Warden et al, 2007) in tendinopathies acquired from highimpact activities such as jumping and running. However, these changes do not necessarily correlate with symptoms or diagnosis of tendinopathy based on clinical examination (Khan et al, 1997;Giza et al, 2013). Given the difference in potential mechanism of injury in esports competitors, namely low-impact but highly repetitive activities, the association between imaging-identified pathophysiological changes and clinically diagnosed tendinopathies may differ and should be investigated.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…(18), the relationship between peroneus brevis tendon tear as seen on MRI was compared to clinical findings. A clinical finding was defined as patient having one of the following symptoms or presentation for peroneal tenderness, weakness, subluxation, snapping, or pain on posterolateral ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 56 patients with positive findings on MRI, only 27 had an associated symptoms on clinical examination. They concluded that MRI images had a positive predictive value of 48% for presence of true tendon tear (18). In our patient population, the positive predictive value for peroneus brevis tendon tear using MRI was 92.31% (Table 2).…”
Section: Discussionmentioning
confidence: 99%